Smoke Signals from Samarcand : The 1931 Reform School Fire and Its Aftermath - Bennett, Barbara, 1959- (Book collections on Project MUSE., 2018)
"In 1931, sixteen poor white teenage girls at Samarcand Training School for Girls in Moore County, North Carolina, were accused of burning down two buildings in protest against living conditions at the school. They were called incorrigible, troublesome, and vixens by the administration and the press, and they were put on trial for their lives. Their lawyer, who volunteered to defend the girls, was a newly licensed woman named Nell Battle Lewis, known most as a journalist who spoke for the voiceless in society and only the second woman lawyer to try a case in Raleigh. The time leading up to the sensational trial revealed the girls were victims of class, sex, and eugenics. Partly a retelling of the dramatic story and partly a treatise on southern society in the early twentieth century, Smoke signals from Samarcand tells a tale of the benighted South and the victims of that time and place"--